Beyond kenoticism: Why the suffering God had to become man - Sarot, Marcel (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
From its very beginnings Christianity has believed that the redemption of humanity was dependent upon Incarnation and cross, while simultaneously maintaining the impassibility of the Father. Only in and through the Incarnation could God suffer. In the last century, belief in the impassibility of God has become a minority position; the majority position has become that God is passible. The cross of Christ is then mostly seen as a revelation of that passibility, important but not essential to human salvation. In this paper I argue that belief in God’s passibility does not necessitate us to give up the idea that the cross of Christ is constitutive of our salvation. On the contrary, once we have abandoned the limited interpretation of redemption as mere forgiveness and restored the original ideal of redemption as a radical healing of human nature, we can gain some insight why God had to become human to transform human nature from the inside out, as He has done in the Incarnation. Drawing on Aquinas and on C.S. Lewis, I suggest that the idea of good infection and the model of the church as the body of Christ can give us some insight in how the Incarnation and passion of Christ can be effective for all of us.